2000
DOI: 10.1207/s15327019eb1001_4
|View full text |Cite
|
Sign up to set email alerts
|

Respecting Autonomy in Difficult Medical Settings: A Questionnaire Study in Japan

Abstract: Some people in Japan are still comfortable with the paternalistic role of doctors, but others wish that their own decisions would receive a greater amount of respect. A total of 747 students of universities and colleges and 114 parents of these students participated in a questionnaire survey. Most of the participants thought that autonomy should be respected in situations involving death with dignity and euthanasia, whereas it should not be respected in attempted suicide and involuntary admission of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Japan has a long tradition of physician paternalism [24] as also seen in many other countries [25-27]. Ishiwata suggested that two deeply seated factors are major contributors to the paternalism of Japanese physician – an absence of the spirit of informed consent on the physician's side, and the practice of omakase (entrusting one's care to one's family and physician, on the assumption that they will make the decisions most beneficial or appropriate to oneself) on the patient's side [28].…”
Section: Discussionmentioning
confidence: 99%
“…Japan has a long tradition of physician paternalism [24] as also seen in many other countries [25-27]. Ishiwata suggested that two deeply seated factors are major contributors to the paternalism of Japanese physician – an absence of the spirit of informed consent on the physician's side, and the practice of omakase (entrusting one's care to one's family and physician, on the assumption that they will make the decisions most beneficial or appropriate to oneself) on the patient's side [28].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of knowledge may reflect inadequate patient education by health care providers. The medical health care system in Asia is historically a paternalistic one [27, 28]. Singaporean patients, unlike Western patients, tend not to ask questions or actively seek information from health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fact that someone else was making decisions about a medical treatment that one was receiving was never questioned. This de-pendent model is gradually changing to an autonomous decision-based model [43]; however, legislation mandating information regarding AD to elderly patients over the age of 75 years may be required to break through this psychological dependency. In parallel, providing a common forum within the region for health care providers, care managers, and citizens to discuss successful dying at home will also lead to reformation of awareness.…”
Section: Obstacles Preventing the Effective Function Of Acp: The Highmentioning
confidence: 99%